1996
DOI: 10.1111/j.0022-3646.1996.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

AMPHIDINIUM OPERCULATUM VAR. NOV. GIBBOSUM (DINOPHYCEAE), A FREE‐SWIMMING MARINE SPECIES PRODUCING CYTOTOXIC METABOLITES1

Abstract: A single‐cell isolate of Amphidinium from the northern Caribbean Sea was identified as A. operculatum Clap. et Lack. var. nov. gibbosum Maranda et Shimizu based on a morphological and ultrastructural study. This free‐swimming dinoflagellate, which was found to produce potent antitumor metabolites, is elongate and asymmetrical. It is compared with two close relatives A. klebsii Kofoid et Swezy and A. carterae Hulburt. Amphidinium operculatum var. gibbosum can be distinguished from A. klebsii on the basis of sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The strains analyzed in this study previously found to produce amphidinolides or amphidinols, biotoxins produced by some Amphidinium species, were the strain of A. carterae , CAWD57 (Houdai et al 2001), and the strain of A. gibbosum SI‐36‐5 (Maranda and Shimizu 1996). A further strain, which appears to be of A. gibbosum , has also been reported in the literature to produce amphidinolides (Kobayashi et al 1991).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The strains analyzed in this study previously found to produce amphidinolides or amphidinols, biotoxins produced by some Amphidinium species, were the strain of A. carterae , CAWD57 (Houdai et al 2001), and the strain of A. gibbosum SI‐36‐5 (Maranda and Shimizu 1996). A further strain, which appears to be of A. gibbosum , has also been reported in the literature to produce amphidinolides (Kobayashi et al 1991).…”
Section: Discussionmentioning
confidence: 97%
“…This species has been found as an endosymbiont in the flatworms Amphiscolops langerhansii , Amphiscolops sp., and Haplodiscus sp. isolated from Florida, USA (Taylor 1971a,b, Blanco and Chapman 1987, Trench and Winsor 1987) as well as free‐living in the plankton from the U.S. Virgin Islands (Maranda and Shimizu 1996).…”
Section: Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have occupied the leading position in the search for new drugs and base model structures in life sciences for the determination of mechanisms of functioning of biosystems [2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…Up to now, more than 30 amphidinolides A-Y and related substances have been isolated and studied [2,3]. Amphidinolides possess a unique structure and exhibit very high cytotoxicity and are therefore potential anti-tumor agents, which attract attention of researchers in the fields of chemistry, biology, and medicine over several decades [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%